Biochemical and Ultrastructural Cardiac Changes Induced by High-Fat Diet in Female and Male Prepubertal Rabbits - Dina Sibouakaz; Khira Othmani-Mecif; Amirouche Fernane; Abdennour Taghlit; Yasmina Benazzoug (Analytical Cellular Pathology)
Early weight gain induced by high-fat diet has been identified as a predictor for cardiac disease, one of the most serious public health problems. Our goal is to study the influence of a HFD on biochemical, oxidant stress parameters, and the cardiac ultrastructure in both male and female prepubertal models. Experiments were carried on 24 prepubertal New Zealand white rabbits, randomly assigned to male and female control (MC and FC, resp.) or HFD (MHFD and FHFD, resp.) groups (n=6) for 3 months. Body and heart weights and some biochemical and oxidative stress parameters such as lipids, calcium, CKMB, MDA, uric acid, ascorbic acid, and AOA are evaluated in plasma and the left ventricle. Under HFD effect, plasma parameters, such as lipids (TL, PL, and LDL-C), MDA, and CK-MB, increase more significantly in male than in female groups, when AA decreases. Some cardiac parameters such as TG and UA increase, when AA and AOA decrease; these variations are more significant in FHFD. In both male and female rabbits, HFD caused changes in heart ultrastructure, junctional complexes, mitochondria size and form, and so on. Early HFD feeding induced overweight, oxidative stress, and metabolic alterations in plasma and the heart of prepubertal rabbits, whereas lipotoxicity has especially a negative impact on male plasma but affects more the female heart ultrastructure.